Analisis Efisiensi Waktu dan Biaya Metode Konvensional dan Steel Deck pada Pekerjaan Deck Slab Jembatan Jalan Tol - Kodrat Insany Taqwim (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates the comparative efficiency of conventional cast-in-situ and steel deck methods for bridge deck slab construction in the Kapuk–Teluknaga–Rajeg Toll Road Project Phase I, Banten Province, Indonesia. The research applies a field-based empirical case study design with a quantitative approach, using primary data from site observations and structured interviews, and secondary data from shop drawings, project specifications, and cost documents. Cost estimation was conducted using unit price-based analysis following AHSP standards regulated by Permen PUPR No. 28/PRT/M/2016, while construction duration was calculated based on actual productivity and activity sequencing. The results indicate that the conventional method required 17 working days with a total cost of Rp 592,003,970, whereas the steel deck method required only 8 working days with a total cost of Rp 553,984,460. These findings demonstrate that steel deck provides a 52.94% reduction in construction time and a 6.42% cost saving. The study further shows that steel deck shifts project cost structure from labor-intensive operations to controlled material-based execution, improving schedule reliability and construction productivity.